Normalisai Pembelajaran Ekonomi Melalui Kolaborasi Problem Based Learning Dan Mind Mapping, Motivasi Berprestasi Terhadap Hasil Belajar - Ihsan Ihsan; Muhammad Nur Arofah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
This research is a quantitative quasi-experimental non-equivalent control group pretest-posttest design. The data analysis technique used factorial design 2×2 (two-way Anova) and t test. Research location at SMA NW Suralaga in the even semester of TP. 2020/2021. The research subjects of class XI IPS are 43 students who are divided into two classes. The results showed, (1) There was a significant difference in learning outcomes between the experimental group (collaborating problem-based learning and mind mapping) which was better than the control group (conventional) with an effect of 70.48%. (2) There is a significant difference in the acquisition of learning outcomes between groups of students who have high achievement motivation better than groups of students who have low achievement motivation with an effect of 10.83%. (3) At the level of achievement motivation which are both high and (4) low, there is a significant difference in learning outcomes between the experimental group (problem-based learning collaboration and mind mapping) which are better than the control group. (5) There is a significant difference in the achievement of learning outcomes between groups of students with low achievement motivation who study with collaborative problem-based learning and mind mapping models better than groups of students with high achievement motivation who study conventionally. (6) There is a significant interaction effect of problem-based learning and mind mapping collaboration, achievement motivation on student learning outcomes. Another finding in this study also proves that the conventional learning model is only suitable for students who have high achievement motivation and is fatal if applied to groups of students with low motivation, because it has implications for lower student learning outcomes.